Gender and Eroticism in Contemporary Art from South Africa - Pawłowska, Aneta (Werkwinkel, 2017)
The aim of this article is to present the interaction between the history of lesbian and gay culture and its identity on the one hand, and the connection between the visual art or visual culture on the other hand. This essay endeavors to interpret the different meanings attached to sexual identities by examining the diverse artistic activities of a variety of artists: both men and women (e.g. Steven Cohen, Clive van den Berg, Andrew Verster, Nicolas Hlobo, Jean Brundrit, Zanele Muholi). Employing an intersectional analytical approach, the article shows that the identity of art is constructed alongside a person’s multiple identities, such as race, gender, family ties, religion and class. The main research question is whether in today’s visual art originating from South Africa, which is characterized by a hegemony of heterosexual stereotypes, there is a significant place for gender oriented art?